Police Policy in Kudus Resort Reveals Crime Conducted by Biological Mother to Biological Child - Tri Mulyono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Interest in this research are to understand policy of Kudus Police in uncovering criminal acts committed against the biological child's by biological mother. This research is empirical legal research, the research is based on analysis of law enforcement against criminal acts committed against the biological child’s by biological mother, quantitatively analyzed inhibiting factors and solutions in law enforcement against criminal acts committed against the biological child’s by biological motherPenal mediation in criminal acts of persecution carried out due to several factors, among which are both economical in terms of both cost and time, factors fostering good relations because in general the party and the victims of family relations, neighbors, and friends.The legal consequences of penal mediation in criminal acts of persecution that is if the penal mediation process is successful, the process of investigation in police Mangala stopped and will not proceed to court. Perpetrators and victims signed the act of peace. In addition, the offender must sign an agreement not to repeat the mistakes again.A dilemma that is not easy in-swatch solution. On the one hand, domestic violence remains a force, an action which caused no casualties, the state has determined that the culprit may be a criminal. On the other hand, if the perpetrator in the crime, the family will bear the shame, domestic unity is threatened, there will be a long judicial process and air-late-late. If the perpetrator is a breadwinner in the household, the family will lose the main breadwinner.Keywords: Crime; Biological Mother; Biological Children.